LIFE SATISFACTION AND POSITIVITY LEVELS OF MUS WORKERS OF PROVINCIAL DIRECTORATE OF YOUTH AND SPORTS - Şekeroğlu, Mustafa Önder (My University, 2019)
The purpose of this study is to determine the life satisfaction and positivity levels of the personnel working in different units of the Mus Youth and Sports Provincial Directorate. In this study conducted on 87 staff; The levels of life satisfaction and positivity of the personnel were determined, and the levels of life satisfaction and positivity were examined in terms of socio-economic, demographic and descriptive characteristics. In this research, a general scanning model, which is one of the descriptive research methods, is applied. In the study, with the personal information form developed by the researchers, Life Satisfaction Scale developed by Diener, Emmons, Laresen and Griffin (1985) and Positivity Scale developed by Caprara, Alessandri, Eisenberg, Kupfer, Steca, Caprara and Abela (2012) were used. In the analysis of data, T-test and multiple comparisons anova test were used for two independent groups. Whether the data provides the assumption of normality is measured by the skewness and kurtosis test. The data collected from the participants within the scope of positivity level research; mann whitney u test and multiple comparisons for two independent groups were analyzed using Kruskal Wallis. As the result of the analysis did not provide the normality assumption, it was decided that it was suitable for the application of nonparametric tests.In this study, life satisfaction and positivity levels of the participants were affected by income levels; It was found that age, gender, marital status and educational status did not cause statistically significant difference in life satisfaction and positivity level.

Bu çalışmanın amacı, Muş Gençlik ve Spor İl Müdürlüğünün farklı birimlerinde görev yapan personelin yaşam doyumu ve pozitiflik düzeylerini belirlemektir. 87 personel üzerinde yürütülen bu çalışmada; personelin yaşam doyumu ve pozitiflik düzeyleri belirlenmiş, yaşam doyumu ve pozitiflik düzeyleri sosyo-ekonomik, demografik ve tanımlayıcı özellikleri açısından incelenmiştir. Bu araştırmada betimsel araştırma yöntemlerinden biri olan, genel tarama modeli uygulanmıştır. Çalışmada, araştırmacılar tarafından geliştirilen kişisel bilgi formu ile Diener, Emmons, Laresen and Griffin (1985) tarafından geliştirilen Yaşam Doyum Ölçeği ile Caprara, Alessandri, Eisenberg, Kupfer, Steca, Caprara and Abela (2012) tarafından geliştirilen Pozitiflik Ölçeği kullanılmıştır. Verilerin analizinde, bağımsız iki grup için T-testi ve çoklu karşılaştırmalar anova testi kullanılmıştır. Verilerin normallik varsayımını sağlayıp sağlamadığı çarpıklık ve basıklık testi ile ölçülmüştür. Pozitiflik düzeyi araştırması kapsamında katılımcılardan toplanan veriler; bağımsız iki grup için mann whitney u testi ve çoklu karşılaştırmalar Kruskal Wallis kullanılarak analiz edilmiştir. Analiz sonucu çıkan değerlerin normallik varsayımını sağlamadığı için nanparametrik testlerin uygulanmasına uygun olduğuna karar verilmiştir. Bu çalışmada katılımcıların yaşam doyum ve pozitiflik düzeylerinin gelir düzeylerinden etkilendiği; yaş, cinsiyet, medeni durum ve öğrenim durumlarının yaşam doyum ve pozitiflik düzeyi üzerinde istatistiksel olarak farklılığa neden olmadığı saptanmıştır.
Keywords: Eğitim, Eğitim Araştırmaları; Spor Bilimleri